Life cycle of Arthroschista hilaralis (Lepidoptera: Pyralidae) on Jabon trees (Anthocephalus cadamba Miq) - Selvi Chelya Susanty; Noor Farikhah Haneda; Mansur, Irdika (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Arthroschista hilaralis is a defoliator pest. Currently, a great number of these insects are attacking Jabon trees, causing a high degree of damage. This study aimed to assess the life cycle of A. hilaralis on Jabon (Anthocephalus cadamba Miq.) The study was conducted by examining each stage of A. hilaralis life development, including the body size and the time required for each stage of A. hilaralis development. The results showed that the average time A. hilaralis took to complete a life cycle was 25.1 days, consisting of egg stage 2.7 days; larva 12.6 days, pupa 6.9 days and pre-oviposition of imago 2.9 days. Pest management action is required on a regular basis to control this pest development due to the high level of development and the rapid rate of growth of A. hilaralis.